An Atomic Receiver for AM and FM Radio Communication - Anderson, David Alexander; Sapiro, Rachel Elizabeth; Raithel, Georg (IEEE transactions on antennas and propagation, 2021)
Radio reception relies on antennas for the collection of electromagnetic fields carrying information, and receiver elements for demodulation and retrieval of the transmitted information. Here, we demonstrate an atom-based receiver for AM and FM microwave communication with a 3 dB bandwidth in the baseband of ~100 kHz that provides optical circuit-free field pickup, multiband carrier capability, and inherently high field sensitivity. The atom-based receiver exploits field-sensitive cesium Rydberg vapors in a centimeter-sized glass cell, and electromagnetically induced transparency, a quantum-optical effect, as a readout of baseband signals modulated onto carriers with frequencies ranging over four octaves, from C -band to Q -band. Receiver bandwidth, dynamic range and sideband suppression are characterized, and acquisition of audio waveforms of human vocals demonstrated. The atomic receiver is a valuable receiver technology because it does not require antenna structures and is resilient against electromagnetic interference, while affording multiband operation in a single compact receiving element.